High efficient room temperature phosphorescent materials constructed with methylene molecular configuration - Wang, Jian (Frontiers in Chemistry, 2022)
In this work, we have investigated several pure organic room temperature phosphorescent materials with donor-methylene acceptor configurations with relatively different quantum efficiency. The results show that the introduction of methylene functional group in room temperature phosphorescent materials based on donor-acceptor configuration is more favorable for obtaining higher phosphorus quantum efficiency in crystal phase environment. More importantly, our calculations reveal the root cause of the excellent quantum efficiency performance after the introduction of methylene groups. The results show that the introduction of methylene can inhibit the structural deformation of molecules during the excited state transition process and give them higher interaction. Moreover, in the donor-acceptor configuration, the heavy atom effect is more favorable to the formation of π-x (X=Br) interaction to accelerate the occurrence of intersystem crossing and achieve a higher intersystem crossing rate. Therefore, the donor-methylene-acceptor molecule is expected to improve the quantum efficiency of room temperature phosphorescence, and the addition of heavy atoms is more conducive to prolong the life of room temperature phosphorescence. This work provides a useful reference for rational design of room temperature phosphorescent materials with high efficiency and long life.